(untitled) (Jurnal Bahasa, 2018)
This article discusses the partial reduplication of the Malay dialect of Urak Lawoi’ Laem Tukkae (MdULLT) in the province of Phuket, Thailand. The objective of this article is to analyse the process of partial reduplication within the MdULLT. In order to obtain primary data, an interview with five informants above the age of 50 from the area of Laem Tukkae, Phuket was carried out. This data was processed and analysed using the autosegmental theory which is based on Clements model of melodic transfer (1985(a)) and Clement’s Representation Level of Syllable Structure (1985(b)). Findings reveal that MdULLT has two types of partial reduplication, which is the root partial reduplication that ends with an open syllable and the root partial reduplication that ends with a closed syllable. Examples of the root partial reduplication ending with open syllables are /bini/ [ni.bi.ni] bebini (women), /rama/ [ma.ra.ma] rerama (butterflies), while the examples for the root partial reduplication ending with closed syllables are /bintaN/ [tak.bi.tak] bebintang (stars) and /rumah/ [mah.ru.mah] rerumah (houses). Based on Clements model of melodic transfer (1985(a)), both types of partial reduplication for the MdULLT are processed using the CVC template. Keyword: process of partial reduplication, open syllables, closed syllables, urak lawoi’